(3fbd JcfhdhLjG GdWGbI GdfhhjI (B: s (3OQGSI JMdjdjI dYbhO EfTGA eMWGJ Gdbhi GdfhhjI(B: (3habkG deJWdHGJ GdLgI GdQbGHjI(B: (3aj EWGQ bGfhf JfXje GdCfTWI GdfhhjI hGdETYGYjI (B/ s - (3CfhQ UHQj YHOGdYXje eMeO UHQg GdSjhjs; (3YGOd eMeO CMeO Ydi s; (3gGfj UdGM SQj GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JJfGhd GdOQGSI fbd JcfhdhLjG GdWGbI GdfhhjI ef NdGd JMdjd GdeQGMd GdJj jeQ HgG GdJYGbO Ydi eTQhY dEfTGA hJTZjd eMWI Gdbhi GdfhhjI; HgOa hVY Mdhd Jcad Gdfbd GdMbjbj ddJcfhdhLjG GdfhhjI(B. (3ef NdGd hVY HQfGeL ddeTGQcI GdhWfjI aj LejY eQGMd EfTGA hJTZjd GdeTQhY; HGYJHGQg GdCOGI GdChdi dfbd JcfhdhLjG GdWGbI GdfhhjI(B. (3hPdc HHjGf JbOjQGJ dfSH GdeTGQcI GdeMdjI GdcdjI aj EfTGA hJTZjd eMWI Gdbhi GdfhhjI ef cd eG gh eJGM eMdjkG(B: (3hJaUjd HLejY GdCfTWI hGdfXe hGdCOhGJ hGdeYOGJ hGdehGO hGdNOeGJ hGdYfGUQ GdeNJdaI(B: (3GdJj jQi UGMH GdYed Cfg ojrepcf Cf jDOjgG Ch jfJLgG eMdjkG(B: (3hhVY GdHfi GdJMJjI GdUfGYjI(B. (3eY eQGYGI JbOje eGdc GdJcfhdhLjG cGaI GdhKGFb GdJj JUa JcfhdhLjG EfTGA hJTZjd eMWI Gdbhi GdfhhjI ef JUejeGJ(B: (3hQSheGJ(B: (3hNQGFW(B: (3hUhQ(B: (3hHQGeL MGSH Bdj(B: (3Edi ZjQ Pdc ef GdhKGFb GdJj JUa GdJcfhdhLjG(B: (3hcPdc JOQjH GdYGedjf dOi UGMH GdYed Ydi GcJSGH GdegGQGJ hGdNHQGJ GddGReI dGSJjYGH GdJcfhdhLjG(B. (3ceG jJYjf JbOje cGaI GdNOeGJ GdgfOSjI hGdEOGQjI hcPdc GdeSGYOGJ GdafjI aj eQGMd JfajP GdeTQhY(B: (3HOAkG ef GdCYeGd GdJMVjQjI GdJj JSHb JfajPg(B: (3heG jJHYgG ef eQGMd JQcjH GdefTCI(B: (3hGNJHGQgG(B: (3hJTZjdgG(B: (3hEUdGMgG(B: (3hUjGfJgG(B. (3hcPdc JbOje GdeSGYOGJ GdafjI aj GdMUhd Ydi bWY GdZjGQ ddefTCI(B: (3haj JQcjHgG(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2017(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B306-325s
Keywords: (3JcfhdhLjG GdWGbI GdfhhjI s; (3WQb GdJYGbO Ydj fbd JcfhdhLjG GdWGbI GdfhhjIs; (3GdTcd GdbGfhfj dYbO fbd JcfhdhLjG GdWGbI GdfhhjIs; (3eYhbGJ fbd JcfhdhLjG GdWGbI GdfhhjI aj GWGQ JYOO GdYbhOs; (3GHQGe YbO JcfhdhLjG GdWGbI GdfhhjIs; (3JfajP fbd JcfhdhLjG GdWGbI GdfhhjIs; (3eMWI Gdbhj GdfhhjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs